2021
DOI: 10.1111/dmcn.15020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sex chromosome number variation on attention‐deficit/hyperactivity disorder symptoms, executive function, and processing speed

Abstract: ABBREVIATIONS NEPSYDevelopmental NEuroPSYchological Assessment SCA Sex chromosome aneuploidy AIM To study sex differences in attention-deficit/hyperactivity disorder (ADHD) symptoms, we explored whether X chromosome absence or excess is independently associated with deficits in attention and hyperactivity, executive function, and processing speed. METHOD We assessed 116 children (ages 3y 10mo-11y 11mo, mean 8y 5mo, SD 1y 11mo) with a variable number of sex chromosomes: 36 females with Turner syndrome (45, X0),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…brain connectome organizations) but also to predict core clinical symptoms of ADHD (e.g. poor executive function) 90–92 . Despite shared chromosomal variants in cross‐disorder diagnostics (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…brain connectome organizations) but also to predict core clinical symptoms of ADHD (e.g. poor executive function) 90–92 . Despite shared chromosomal variants in cross‐disorder diagnostics (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…poor executive function). [90][91][92] Despite shared chromosomal variants in cross-disorder diagnostics (e.g. autism, bipolar disorders and schizophrenia), such X-linked changes were found to be relatively specific for ADHD by showing the common chromosomal alternations of other neuropsychiatric disorders into 3, 10, and 16 (rather into X).…”
Section: Gene-set Decoding Of Pls Componentsmentioning
confidence: 99%
“…A study showed that X chromosome variation may explain ADHD prevalence discrepancies between males and females. Therefore, X-linked gene dosage or genetic variations may explain why ADHD is more common in males than females [ 23 ]. We also found that ADHD was more common at younger ages, as shown in a previous study where ADHD was more prevalent when children started school [ 21 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cognitive profile of Turner syndrome can vary widely, still it is often described with an overall intellectual ability within the normal range but with an uneven profile characterized by relative strengths in verbal functions compared to visuo-spatial abilities 6 8 . Other impairments commonly associated with Turner syndrome include impaired executive functions, such as working memory, cognitive flexibility, and attention 9 11 .…”
Section: Introductionmentioning
confidence: 99%